2022
DOI: 10.3389/fpsyg.2022.833372
|View full text |Cite
|
Sign up to set email alerts
|

Internal Persistence and External Support—What Makes Chinese Teachers of the Mathematically Gifted Stick to Their Post?

Abstract: Mathematically gifted students are precious human resources, educators of which make a great difference in helping them realize their potential. The retention of qualified teachers of mathematically gifted students is an issue worthy of in-depth exploration. In China, mathematics competitions are an important part of mathematics gifted education, and the teaching of the Mathematical Olympiad is a challenging profession with a high attrition rate. This qualitative study takes four seasoned and outstanding Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“… Hoth et al (2016) found that teachers who had difficulty with logical reasoning and understanding mathematical structures also had difficulty identifying mathematically gifted students. Sunzhong et al (2022) takes four seasoned and outstanding Chinese teachers as cases, and uses the thematic analysis method based on Herzberg’s two-factor theory to analyze why they can persist in the field of Mathematical Olympiad teaching for more than 20 years. Baker et al (2022) find that teachers view their students’ participation in mathematics competitions as being important, with the biggest barrier to participation being that there are not enough competitions at appropriate levels available in Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“… Hoth et al (2016) found that teachers who had difficulty with logical reasoning and understanding mathematical structures also had difficulty identifying mathematically gifted students. Sunzhong et al (2022) takes four seasoned and outstanding Chinese teachers as cases, and uses the thematic analysis method based on Herzberg’s two-factor theory to analyze why they can persist in the field of Mathematical Olympiad teaching for more than 20 years. Baker et al (2022) find that teachers view their students’ participation in mathematics competitions as being important, with the biggest barrier to participation being that there are not enough competitions at appropriate levels available in Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the teachers in this study, their interactions with family members and the teaching tasks were included in this system. Long working hours and complex mathematical problems both affect the lives and work of teachers of the mathematically gifted ( Sunzhong et al, 2022 ). The mesosystem involves the relationships and processes that occur between two or more changing, developing settings or people ( Bronfenbrenner, 2005 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations